FACTORS CONTRIBUTING TO EXISTENCE OF UNETHICAL PRACTICES IN THE INSURANCE INDUSTRY - Kajwang, Ben (Journal of Advanced Sociology, 2022)
Purpose: The success of the insurance industry vastly depend on the ethical behavior patterns of insurance companies, insurance agents, or insurance brokers as they are the persons who have direct relationships with customers. Ethical behavior patterns in turn build up the customer's satisfaction and trust towards the insurance industry. Therefore, the insurance industry stakeholders must have the knowledge of the key factors that influences existence the unethical behavior in insurance industry if they want to ensure the ethical behavior prevail in the industry. Different factors contribute to these ethical behavior patterns and organizational factors are more important among them. The main purpose of this study was to identify the factors contributing to existence of unethical practices in the insurance industry. Methodology: In this study, a systematic search was carried using search engines such as Google Scholar, Google Books, Semantic Scholar, Science.gov and ResearchGate, using the keywords; "ethical practices" and "insurance industry". In total, 52 papers, published until between November 2012 and January 2022, were extracted from these databases. After removing duplicates, the titles and abstracts of these articles were reviewed based on the inclusion and exclusion criteria. Inclusion criteria included all types of studies that examine organizational ethical practices. Exclusion criteria included non-English language articles, articles whose full text could not be accessed, and clinical organization articles due to their different nature. After screening the titles and abstracts of the articles, 46 articles were carefully selected for full text review based on inclusion and exclusion criteria and finally, 34 articles were included in the study. Findings: According to the findings, researchers have shown that it is impossible to salvage the public image of insurance industry without ethical behavior patterns of insurance companies, among insurance agents, insurance brokers, insurance customers, and other stakeholders. This study further shows that more effort is required to protect the individual salesperson's reputation as well as that of the entire insurance industry. Ethical behavior has been found to be a key ingredient to the success of every insurance provider and to the insurance industry. Recommendations: This study recommends that insurance providers should place ethical issues first in their core values in order to uphold and maintain integrity and accountability in their services. It is also recommended that the management in the insurance industry should uphold transformational leadership that embraces honesty and integrity in business operations. Moreover, the management of the insurance companies should ensure that all their sales agents have adequate knowledge of their various insurance policies to avoid instances of guesswork, just in efforts to lure customer to subscribe to the policies, which is merely aimed at lifting up the earnings of the respective sales agents. It is also recommended that insurance firms should increase their audit frequency in to detect fraudulent claims.